Legal Protection for Termination of Employment In the Era of Covid-19 Pandemic (Comparative Study of Islamic Law and Positive Law in Indonesia) - Maraliza, Helma; Narwati, Lily May; Permata, Helen Aulia; Muslim, Muslim (Universitas Islam Negeri Raden Intan Lampung, 2022)
The purpose of this research is the legal protection for Termination of Employment in the era of the COVID-19 pandemic according to Islamic law and Indonesian positive law as well as the similarities and differences between the two. The research method used in this research is comparative descriptive, with a content analysis approach. This approach used an in-depth discussion of the contents of written information, systematically and objectively analyzed the facts, characteristics, and the relationship between existing elements or certain phenomena and can then be compared to theory. According to Islamic law, legal protection for workers against layoffs is part of the purpose of Islamic law. Namely to maintain life and property to achieve happiness in the world through a good and honorable life (hayyah thayyibah). Therefore, it must be carried out with principles such as human freedom, human dignity, justice, and anti-discrimination, as well as fair wages. In contrast, according to positive law, workers' legal protection for termination of employment can occur because the company is closed due to force majeure, and the entrepreneur is obliged to pay severance pay, long service pay and compensation rights pay that must be received by the worker. The difference is that Islamic law is not regulated in detail regarding the provision of severance pay, long service pay, and compensation rights pay that should be received as in positive law. However, in Islamic law, it is carried out following the agreement (akad) that has been made and agreed to. Therefore, there is no dispute due to injustice committed by one of the parties.Keywords: Islamic Law, Positive Law, Covid-19 Pandemic, Layoffs, Legal Protection